Pandemic and the pandemony of corruption in third world countries The high failure of action and the result of corruption crimes in emergency situations - Alcalde Muñoz, Elvis Jorge (2020)
This article gives a criminological perspective in relation to modern criminal law and the figure of the devaluation of the action and the result in special crimes such as corruption in situations of national emergency, understanding the figure of devaluation as part of the unlawful element of the crime. On the other hand, it addresses the issue of public opinion as an important factor in the positive or negative assessment of an allegedly criminal act and its participation as a pressure and / or interest group before the State authorities against a fact of social relevance.